2016
DOI: 10.3892/etm.2016.3603
|View full text |Cite
|
Sign up to set email alerts
|

Osthole decreases renal ischemia-reperfusion injury by suppressing JAK2/STAT3 signaling activation

Abstract: Renal ischemia-reperfusion (I/R) injury is a major cause of acute kidney injury. The pathogenetic mechanisms underlying renal I/R injury involve inflammation, oxidative stress and apoptosis. Osthole is a coumarin derivative that exhibits potential anti-inflammatory activity. The aim of the present study was to investigate the effect of osthole in renal I/R injury and its underlying mechanism. Renal I/R injury was induced by clamping the left renal artery for 45 min followed by 24 h reperfusion with the contral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…Studies have shown that one IRI can initiate a variety of signaling pathways, among which highly conserved JAK2/STAT3 signaling pathways can be reactivated and participate in the regeneration and repair of renal tubular epithelial cells by suppressing NF-κB activation [ 11 , 12 ]. Therefore, we examine the effect of Curcumin on JAK2/STAT3 signaling in IRI.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that one IRI can initiate a variety of signaling pathways, among which highly conserved JAK2/STAT3 signaling pathways can be reactivated and participate in the regeneration and repair of renal tubular epithelial cells by suppressing NF-κB activation [ 11 , 12 ]. Therefore, we examine the effect of Curcumin on JAK2/STAT3 signaling in IRI.…”
Section: Discussionmentioning
confidence: 99%
“…Photographs of the kidney cortex of each mouse were obtained from five random fields for analyzing the histopathology changes. The histopathological changes were evaluated by a pathologist in a blinded fashion according to the degree of tubular necrosis, hemorrhage and cast formation as follows: 0, no change; 1, change affecting less than 25% of the field; 2, change affecting 25–50% of the field; 3, change affecting 50–75% of the field; 4, change affecting greater than 75% of the field [13]. The other half of the kidney samples was also assessed by transmission electron microscopy (Hitachi, Tokyo, Japan) under uranyl acetate and lead citrate double staining.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the effects of STAT3 on inflammation, one study showed that the activation of phosphorylated STAT3 during myocardial I/R reduced the levels of inflammatory factors such as IL-6 and TNF-α, but other studies found that suppressing JAK2/STAT3 signaling resulted in lower levels of IL-6, IL-8, and TNF-α [51,52]. Therefore, STAT3 activation and phosphorylation could be beneficial or detrimental based on different conditions.…”
Section: Oxidative Medicine and Cellular Longevitymentioning
confidence: 99%